2021
DOI: 10.3390/min11090984
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Geochemistry of Scheelites in the Tongshankou Deposit in Daye, Hubei, China: Implication for REE Substitution Mechanism and Multistage W Mineralization Processes

Abstract: The Tongshankou skarn deposit in the Edong ore district is a typical metasomatic deposit associated with adjacent granodiorite porphyry and carbonate rocks. Using comprehensive microscopic observations, mineralogical and geochemical analysis, scheelite grains in the skarns can be classified into three major types, showing multi-stage mineralization characteristics. In the redox fluid environment, scheelites that occur with garnets usually have affinity to garnets, while in later skarn phases others exist with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The Diantan Sn-Pb-Zn polymetallic deposit in Tengchong, Yunnan, is located in the Tengchong Block of the Southwest Three Rivers Tethys tectonic domain. It represents the northern extension of the well-known southeast Asian tin polymetallic mineralization belt [13][14][15][16][17], primarily yielding Sn, Pb, Zn, and fluorite deposits. Recent mineral exploration has shown that the granite associated with the Sn-Pb-Zn deposits in the mining area is highly differentiated and evolved, suggesting significant mineralization potential for key metals such as Li and Rb.…”
Section: Introductionmentioning
confidence: 99%
“…The Diantan Sn-Pb-Zn polymetallic deposit in Tengchong, Yunnan, is located in the Tengchong Block of the Southwest Three Rivers Tethys tectonic domain. It represents the northern extension of the well-known southeast Asian tin polymetallic mineralization belt [13][14][15][16][17], primarily yielding Sn, Pb, Zn, and fluorite deposits. Recent mineral exploration has shown that the granite associated with the Sn-Pb-Zn deposits in the mining area is highly differentiated and evolved, suggesting significant mineralization potential for key metals such as Li and Rb.…”
Section: Introductionmentioning
confidence: 99%